2011
DOI: 10.1073/pnas.1100087108
|View full text |Cite
|
Sign up to set email alerts
|

Chiral symmetry breaking by spatial confinement in tactoidal droplets of lyotropic chromonic liquid crystals

Abstract: In many colloidal systems, an orientationally ordered nematic (N) phase emerges from the isotropic (I) melt in the form of spindle-like birefringent tactoids. In cases studied so far, the tactoids always reveal a mirror-symmetric nonchiral structure, sometimes even when the building units are chiral. We report on chiral symmetry breaking in the nematic tactoids formed in molecularly nonchiral polymer-crowded aqueous solutions of low-molecular weight disodium cromoglycate. The parity is broken by twisted packin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
173
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(177 citation statements)
references
References 64 publications
(85 reference statements)
2
173
2
Order By: Relevance
“…In particular, one anticipates that achiral substances can be transformed, at most, into a racemic mixture of equally represented enantiomers, or into an enantiopure system with equal probability for the two enantiomers. Apart from the handedness imparted by proto-chiral organizing surfaces 3 , oriented reacting interfaces 4 , and aligning 5 or confining 6 boundaries, the balance above may be broken under the intervention of one within a few physical forces of signed helicity 7,8 , or through the effect of a chiral chemical modifier. In general terms, there is still the pending issue of whether a chiral physical force may be opposed in an effective way to a chiral chemical intervention.…”
mentioning
confidence: 99%
“…In particular, one anticipates that achiral substances can be transformed, at most, into a racemic mixture of equally represented enantiomers, or into an enantiopure system with equal probability for the two enantiomers. Apart from the handedness imparted by proto-chiral organizing surfaces 3 , oriented reacting interfaces 4 , and aligning 5 or confining 6 boundaries, the balance above may be broken under the intervention of one within a few physical forces of signed helicity 7,8 , or through the effect of a chiral chemical modifier. In general terms, there is still the pending issue of whether a chiral physical force may be opposed in an effective way to a chiral chemical intervention.…”
mentioning
confidence: 99%
“…29 Indeed, studies have demonstrated that LCLCs in micro-scale confinement form unique, elastic-property-dependent configurations. 30,31 In this contribution we manipulate the patterning of LCLC films within micropost arrays by modulating the LCLC mesophases and elastic properties via concentration changes during a drying process. We discover a preferred alignment in nematic films governed by elastic interactions with postplacement geometry, and we observe multiple fascinating stable patterned states of the columnar phase.…”
Section: Introductionmentioning
confidence: 99%
“…Elasticity-driven chiral symmetry breaking is perhaps most readily manifested in confined LCs (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), wherein surface anchoring imposes a preferred angle for LC mesogens at the interface of the confining boundary. Topological defects enforced by boundary conditions can play a key role in the symmetry breaking as well, because energetically costly deformations are often concentrated in the vicinity of the defects (35)(36)(37).…”
mentioning
confidence: 99%
“…Liquid crystals (LCs) are soft materials composed of anisotropic mesogens that provide remarkable examples of chiral symmetry breaking arising from elastic anisotropy (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). In essence, an LC can minimize elastic free energy by organizing its achiral units into chiral structures, such as helices and chiral layers, that incorporate twist deformation (7,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation